ATP Triggers Human Th9 Cell Differentiation via Nitric Oxide-Mediated mTOR-HIF1α Pathway - Roy, Suyasha; Awasthi, Amit (Frontiers in Immunology, 2019)
Interleukin 9 (IL-9)-producing helper T (Th9) cells have a crucial effector function in inducing allergic inflammation, autoimmunity, immunity to extracellular pathogens and anti-tumour immune responses. Although the cytokines that lead to the differentiation of human Th9 cells have been identified, other factors that support the differentiation of Th9 cells have not been identified yet. Here we show that the extracellular ATP (eATP) induces the differentiation of Th9 cells. We further show that eATP induces the production of nitric oxide (NO), which creates a feed forward loop in the differentiation of human Th9 cells, as inhibition of purinergic receptor signalling suppressed the generation of human Th9 cells while exogenous NO could rescue generation of Th9 cells even upon inhibition of purinergic receptor signalling. Our findings thus identify that ATP induced nitric oxide potentiate HIF1α-mediated metabolic pathway that leads to IL-9 induction in Th9 cells. Here we identified that the ATP-NO-mTOR-HIF1a axis is essential for the generation of human Th9 cells and modulation of this axis may lead to therapeutic intervention of Th9-associated disease conditions.